The Influence of Human Relations and Self-Efficacy on Job Satisfaction Through Work Motivation as an Intervening Variable on Members of the 1615-07/Sakra Military Rayon Command - Reinaldi Satria Wahyudi, Muhamad; Suryatni, Mukmin (Postgraduate, University of Mataram, 2025)
This study aims to determine: (1) the influence of human relations on the job satisfaction of members of the 1615-07/Sakra Military District Command, (2) the influence of self-efficacy on the job satisfaction of members of the 1615-07/Sakra Military District Command, (3) the influence of human relations on the work motivation of members of the 1615-07/Sakra Military District Command, (4) the influence of self-efficacy on the work motivation of members of the 1615-07/Sakra Military District Command, (5) the influence of work motivation on the job satisfaction of members of the 1615-07/Sakra Military District Command, (6) the influence of human relations on job satisfaction through motivation as an intervening variable of members of the 1615-07/Sakra Military District Command, (7) the influence of self-efficacy on job satisfaction through motivation as an intervening variable of members of the 1615-07/Sakra Military District Command. This study is an associative causal study using a quantitative approach. The population of this study was all members of the 1615-07/Sakra Military Rayon Command totaling 52 members. Data were collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used was path analysis. The results of the study at a significance level of 5% showed that: (1) there is a positive but insignificant influence of human relations on job satisfaction. This is evidenced by the original sample value of 0.057 and has a t-statistic value of 0.216 <1.96. While the P-value> alpha is 0.829> 0.05. (2) there is a positive but insignificant influence of self-efficacy on job satisfaction. This is evidenced by the original sample value of -0.342 and has a t-statistic value of 1.208 <1.96. While the P-value> alpha is 0.227> 0.05. (3) there is a positive and significant influence of human relations on work motivation. This is proven by the original sample value of 0.328 and has a t-statistic value of 2.403 > 1.96. While the P-value < alpha is 0.016 < 0.05. (4) there is a positive and significant influence of self-efficacy on work motivation. This is proven by the original sample value of 0.645 and has a t-statistic value of 4.659 > 1.96. While the P-value < alpha is 0.000 < 0.05. (5) there is a positive and significant influence of work motivation on job satisfaction. This is proven by the original sample value of 1.131 and has a t-statistic value of 3.529 > 1.96. While the P-value < alpha is 0.000 < 0.05. (6) there is a positive and significant influence of human relations on job satisfaction through work motivation. This is proven by the original sample value of 0.370 and has a t-statistic value of 2.014 > 1.96. While the P-value < alpha is 0.044 < 0.05. (7) there is a positive and significant influence of self-efficacy on job satisfaction through work motivation. This is proven by the original sample value of 0.730 and has a t-statistic value of 2.933 > 1.96. While the P-value < alpha is 0.003 < 0.05.